Queuing network approach for building evacuation planning - Ishak, Nurhanis; Khalid, Ruzelan; Baten, Md Azizul; Mohd Nawawi, Mohd Kamal (2014)
The complex behavior of pedestrians in a limited space layout can explicitly be modeled using an M/G/C/C state dependent queuing network.This paper implements the approach to study pedestrian flows through various corridors in a topological network.The best arrival rates and their impacts to the corridors’ performances in terms of the throughput, blocking probability, expected number of occupants in the system and expected travel time were first measured using the M/G/C/C analytical model.These best arrival rates were then fed to its Network Flow Programming model to find the best arrival rates to source corridors and routes optimizing the network’s total throughput.The analytical results were then validated using a simulation model.Various results of this study can be used to support the current Standard Operating Procedures (SOP) to efficiently and safely evacuate people in emergency cases.